Chemical Composition and Antimicrobial Activities of Essential Oils from Nepeta cataria L. against Common Causes of Food-Borne Infections. (17th June 2012) - Zomorodian, Kamiar; Saharkhiz, Mohammad Jamal; Shariati, Samaneh; Pakshir, Keyvan; Rahimi, Mohammad Javad; Khashei, Reza
Abstract : Nepeta cataria L. is traditionally consumed as a food additive. The effects of three different harvest stages of N. cataria essential oils (EOs) against most common causes of food-borne infections were evaluated by broth microdilution method as recommended by the Clinical and Laboratory Standards Institute (CLSI). The chemical composition of the EOs from N. cataria has been analyzed by gas chromatography/mass spectrometry (GC/MS). The analysis of the EOs indicated that 4a- α, 7- α, 7a- β -nepetalactone (55–58%) and 4a- α, 7- β, 7a- α -nepetalactone (30–31.2%) were the major compounds of the EOs at all developmental stages. The results showed that the tested EOs exhibited antimicrobial activities against the food-borne pathogens at concentrations of 0.125–2 μ L/mL. Based on these results, the EO of N. cataria can possibly be used in food products as a natural preservative agent.